2013
DOI: 10.1149/2.008309jss
|View full text |Cite
|
Sign up to set email alerts
|

A Red Long-Lasting Phosphorescence Material Gd9.33(SiO4)6O2:Sm3+and Effect of Oxygen Vacancies on Its Performance

Abstract: A novel red long-lasting phosphorescence material Gd9.33(SiO4)6O2:Sm3+ was reported in this paper. There are two kinds of Gd sites occupied by Sm3+ ions in this host matrix, Gd1 (CN = 9) and Gd2 (CN = 7). The Gd2 site is surrounded by six oxygen atoms bonded to silicon and one free oxygen atom which may be missed easily and then become an oxygen vacancy. A significant sequential enhancement on the afterglow performance of the air-sintered, the vacuum-sintered and the reduction-sintered samples was observed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Moreover, the defects of oxygen vacancies usually appear in the oxide host when a sample is sintered at reducing atmosphere [43]. It was reported that the increase of the Sm 3+ ion doping concentration in Gd 9.33 (SiO 4 ) 6 O 2 : Sm 3+ phosphors resulted in the stable enhancement of the TL peak at 343 K, indicating that quantity of traps increased gradually and also perfected the luminous properties [36]. As shown in Fig.…”
Section: Thermoluminescence Characteristicsmentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, the defects of oxygen vacancies usually appear in the oxide host when a sample is sintered at reducing atmosphere [43]. It was reported that the increase of the Sm 3+ ion doping concentration in Gd 9.33 (SiO 4 ) 6 O 2 : Sm 3+ phosphors resulted in the stable enhancement of the TL peak at 343 K, indicating that quantity of traps increased gradually and also perfected the luminous properties [36]. As shown in Fig.…”
Section: Thermoluminescence Characteristicsmentioning
confidence: 86%
“…In the reports [27,36,42], the TL peak at 343 K in both bZn 3 (PO 4 ) 2 : Mn 2+ and Gd 9.33 (SiO 4 ) 6 O 2 : Sm 3+ and the TL peak at 325 K in Sr 2 SnO 4 : Sm 3+ were all attributed to the defects of oxygen vacancies. Moreover, the defects of oxygen vacancies usually appear in the oxide host when a sample is sintered at reducing atmosphere [43].…”
Section: Thermoluminescence Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…The electric-dipole transition ( 5 D 0 -7 F 2 ) is stronger than the magnetic-dipole transition ( 5 D 0 -7 F 1 ), indicating that Eu 3+ ions occupy a low-symmetry site. 25,26 In GdSr 2 AlO 5 :Eu 3+ , the 5 D 0 -7 F 4 transition at 703 nm is the strongest, which is greatly appropriate for applications in biomedical imaging. 13 Generally, dominant 5 D 0 -7 F 4 transitions are not oen found in the PL spectra of Eu 3+ ions.…”
Section: Photoluminescence Analysismentioning
confidence: 99%
“…43) and Gd 9.33 (SiO 4 ) 6 O 2 :Sm 3+ . 25 It is well known that the oxygen vacancies, which act as electron traps, play major roles in the aerglow time in LLP materials. 43 In the TL curve, the intensity corresponds to the quantity of traps.…”
Section: Thermoluminescence Characteristicsmentioning
confidence: 99%